(untitled) (Proceedings International Conference on Fisheries and Aquaculture, 2022)
Fish and macroinvertebrate diversity was studied in the river Mara Bharali at Tezpur in the Sonitpur district of Assam as no such enumerative works on the river system was done previously. Five sampling stations (MB1, MB2, MB3, MB4 and MB5) covering a stretch of 16.5 kms were selected from Pumpani village (sampling station MB5, N-26º45’10.52" and E92º50’07.93") to Maithan (sampling station MB1, N-26º37’05.69" and E-92º49’34.34"). Fishes and invertebrates were collected and identified following relevant literatures. Thirty four (34) species of fishes of 25 genera, 08 orders and 17 families has been recorded. Cyprinids were found to be the most dominant group with 12 representative species. Twenty (20) species of aquatic insects belonging to 13 families and 7 orders were found. Moreover, six (06) molluscan species belonging to 5 different families were also recorded. Shannon diversity index (H) for macroinvertebrates was highest in sector MB1 (4.468). Pielou equitability index (J) was highest at MB4 (0.9805). The value of Margalef index (Ma) was highest at MB4 (3.831) and lowest at MB3 (1.861). Sector-wise diversity indices of macroinvertebrates reflect the ecological status of river Mara Bharali. The macroinvertebrates of all the sites are evenly distributed as the calculated value of J is close to 1. On the basis of the value of macroinvertebrate diversity index, it may be concluded that river Mara Bharali is quiet healthy at sectors MB1, MB4 and MB5 as the Margalef index is greater than 3. However, sectors MB2 and MB3 are likely to be polluted as the value of Ma is less than 3.